GENDER-SENSITIVE FAMILY RESILIENCE EDUCATION AS A PREFERRED ACTION AMIDST THE DIVORCE TREND IN INDONESIA - Zuhriah, Erfaniah Erfaniah; Fuadi, Suud Suud; Sukadi, Imam Imam; Ashari, Zahrah Salsabillah (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2024)
Gender often becomes an issue in assuming roles in family resilience. Some people believe that maintaining household stability is a responsibility solely entrusted to the husband. However, one of the factors contributing to divorce is the imbalance in household stability resulting from the lack of roles among family members in maintaining family resilience and well-being. This study aims to explore how family resilience education operates in Kemantren Village, Malang Regency. Simultaneously, this article also seeks to examine the implications of gender perspectives on the community in Kemantren Village. The research method used is qualitative, with a sociological approach. This study involves 27 individuals as informants who will fill out questionnaires and also serve as interview subjects to understand the state of family resilience education in Kemantren Village. The study findings indicate that women's roles in the family not only influence overall family dynamics but can also be crucial factors in facing challenges and strengthening family resilience. The insights from family resilience education in Kemantren Village have had a positive impact on the sustainability of their households. Considering women's roles in the context of family resilience is one essential step in addressing the divorce trend in Indonesia